FROM “I DID NOT LEARN ANYTHING” TO “MAKE YOURSELF HEARD.” THE CONSTRUCTION OF POLITICAL SUBJECTIVITIES AND CITIZENSHIPS IN AN EDUCATIONAL INSTITUTION IN BOGOTÁ (2015)
The following article is a summary of an ethnography on the formation of political subjectivities of two students in a school institution characterized by an authoritarian political culture school. We sought to understand how, why and what kind of political subjectivities and citizenships are occurring in young people participating in the various projects of civic education in school, the role played by the various public policies in education, training projects on citizenship of the sed, the Personería and the Contraloría, family, peer groups and memory in the formation of these subjectivities are analyzed. Finally, some pedagogical strategies for ethical and political education at school are proposed school.